Developing Indonesian language learning assessments: Strengthening the personal competence and Islamic psychosocial of teachers - Desi Sukenti; Syahraini Tambak; Charlina Charlina (Institute of Advanced Engineering and Science, 2020)
Research on the assessment of learning has been carried out by many other researchers, but putting Islamic psychosocial and personal competence as a solution has not been found. This study aimed to develop an assessment of Indonesian Language learning for high school teachers by strengthening Islamic psycosocial and personality competencies. Using the ex post facto approach, by distributing questionnaires to 213 Indonesian Language teachers and analyzed using descriptive and regression. This research results in the mastery of teachers about personality competence, Islamic psychosocial, and the assessment of Indonesian Language is the same as medium mastery. Personality competence and Islamic psychosocial as together are very strong in developing the ability to assessment Indonesian Language learning in high school teachers. Islamic psychosocial is predicted to be able to improve the assessment of Indonesian Language high school teacher learning as well as personality competence. This study concludes that personality’s competences and Islamic psychosocial are very significant in developing the assessment of Indonesian Language high school teacher's in learning. This research contribution strengthens the development of the theory of